KARAKTERISASI BATUAN RESERVOAR PERMEABILITAS RENDAH FORMASI BEKASAP BERDASARKAN STUDI PETROGRAFI DAN LINGKUNGAN PENGENDAPAN - PRASETYO , HADI
An integrated petrographic i.e. thin section, x-ray defraction (XRD) and scanning electron microscopy (SEM), and depositional environment study is one of many methods available, which is relatively cheap, and giving quick and accurate results to support reservoir characterization. The objectives of this study are to identify 1950 interval sandstone of Bekasap Formation characters regarding productio n optimization. This research docummented that geologic factors controlled on development strategy and production optimization for the 1950 interval sandstone of Bekasap Formation, which is deposited at an estuarine, tidal dominated delta system. According to lithofacies, the 1950 interval sandstone can be divided into upper and lower parts. The lower part consist of medium grained, conglomeratic cross-bedded and massive sandstone, slightly bioturbated sandstone, mainly arenite type that have horizontalpermeability up to 1,900 mD. On the other hand, the upper one is composed of fine -very fine grained, medium-highly bioturbated sandstone, greywacke type dominated, with horizontal permeability vary from tens up to 200 mD. Diagenetic processes occurred include compaction, recrystallization of mud matrix, precipitation of dolomite, siderite, kaolinite and silica infill pores, slightly replacement of mud matrix and feldspar by dolomite and illite respectively, and partially dissolution of feldspar created secondary pores. In general, reservoir quality development especially horizontal permeability is more controlled by depositional environment factor i.e: grain-size, bioturbatuion and mud matrix content rather than diagenetic process i.e: cementation and dissolution. But, at several depths, both permeability and porosity reduction are significantly controlled by cementation. Permeability reduction is significantly controlled by decreasing grain size and sorting, and increasing both matrix and bioturbatio n content. On the other hand, decreasing both matrix and bioturbation volume, coarser grain size and better sortation are influenced on increasing permeability. Precipitation of dolomite cement is dramatically destroyed both permeability and porosity whereas dissolution is slightly increased both porosity and permeability. Reservoir sensitivities related to production, drilling, and stimulation are controlled by dolomite and siderite that produced calcium-fluoride and/or iron-hydroxide precipitate, and also kaolinite and illite, which are potentially created fine-migration problem. Both technically and economically, horizontal drilling technology as an optimum strategy during developing field and increasing production for low permeability of the 1950 interval sandstone of Bekasap Formation.